2013
DOI: 10.5603/cj.a2016.0056
|View full text |Cite
|
Sign up to set email alerts
|

MiR-103a targeting Piezo1 is involved in acute myocardial infarction through regulating endothelium function

Abstract: Background: Acute myocardial infarction (AMI) is commonly known as the heart attack. The molecular events involved in the development of AMI remain unclear. This study was to investigate the expression of miR-103a in patients with high blood pressure (HBP) and AMI patients with and without HBP, as well as its effect on endothelial cell functions. Methods: MiR-103a expression in plasma and peripheral blood mononuclear cells (PBMCs) was measured by real-time polymerase chain reaction (PCR). The regulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…22) Given that miR-103a was increased in AMI patients, it might be a potential biomarker of MI and could be an index for the diagnosis of AMI. 23) In the current study, we demonstrated that miR-665 was abnormally expressed in I/R-treated rats and might be related to the progression of MI; however, further investigations are needed to understand its mechanism.…”
Section: Discussionmentioning
confidence: 64%
“…22) Given that miR-103a was increased in AMI patients, it might be a potential biomarker of MI and could be an index for the diagnosis of AMI. 23) In the current study, we demonstrated that miR-665 was abnormally expressed in I/R-treated rats and might be related to the progression of MI; however, further investigations are needed to understand its mechanism.…”
Section: Discussionmentioning
confidence: 64%
“…This type of channel directly senses mechanical force and converts environmental signals into intracellular Ca 2+ responses . Properties of PIEZO proteins were soon illustrated in different of eukaryotic cell processes . Both PIEZO family members share physiological and biological similarities.…”
Section: Introductionmentioning
confidence: 99%
“…7 Properties of PIEZO proteins were soon illustrated in different of eukaryotic cell processes. [7][8][9][10][11][12] Both PIEZO family members share physiological and biological similarities. However, their expression patterns are varies in tissues.…”
mentioning
confidence: 99%
“…miRNAs are involved in the regulation of cell proliferation, and some members of them have been determined with pivotal roles in AMI pathogenesis by modulating endothelial cell viability [12,22]. For example, Huang et al reported that miR-103a expression was elevated in AMI patients and involved in the pathogenesis of AMI by regulating the endothelial function, a result manifested by the inhibiting effect of miR-103a on cell proliferation of HUVECs [24]. Bayoumin et al gave evidence for miR-532 as a regulator of cardiac endothelial cell proliferation and deduced that miR-532 had a cardioprotective effect against AMI-associated ischemic heart diseases [22].…”
Section: Discussionmentioning
confidence: 99%